Plan estratégico comunicacional para difundir las actividades micro empresariales que llevan a cabo las personas privadas de libertad del Centro de Rehabilitación social de mujeres de la ciudad de Quito - Barreto Verínaz, Johanna Graciela (2015)
The present investigation the Inca is developed in the feminine Center of Social Rehabilitation of Quito located in the sector, in this site one found a social problem for the lack of knowledge that exists in the company of the productive activities that are carried out inside this center. From this problem there is born the idea of creating a strategic plan of communication that spreads the activities mike managerial that fulfil the internal ones, being this way of resting to his rehabilitation and social rehabilitation, the activities that it takes as an as a way products developed of very good quality help to that the internal ones have an economic contribution and that his time considered as rehabilitation is productive. One of the principal aims of this project is to come to the businessmen entrusted to provide work to small microcompanies, in order to help the internal ones in the increase of contracts to value his workforce generated an economic revenue for them, pitifully for the lack of external knowledge not the products that are made inside the Centers of Social Rehabilitation do not manage to reach an equitable competition with the products that are realized in others mike companies, determined to the plan as the mechanism to achieve that the internal ones reach to the company with his labor development, and in a personal way in his rehabilitation.